(untitled) (Community Based Medical Journal, 2023)
A cross-sectional, descriptive study was done on 150 (70 right and 80 left) fully ossified dry human scapulae of Bangladeshi people to find out the variation in length and breadth of the acromion process. Sample collection was carried out in the Department of Anatomy, Mymensingh Medical College, Bangladesh, between January and December of 2019. Any kind of damaged or broken scapulae were excluded to maintain standard measurement. Length and breadth were measured with the help of digital Vernier slide calipers. The mean (±SD) length was 41.77±5.87 mm and 40.84±6.262 mm on right and left sided scapulae respectively and the mean (±SD) breadth was 22.19±3.08 mm on right sided scapulae and 22.1±2.69 mm on left sided scapulae. These data are important to compare Bangladeshi scapulae to those from various other races that could contribute to demographic studies of shoulder disease probability and management in Bangladeshi population. CBMJ 2023 July: Vol. 12 No. 02 P: 183-187